Denver Developmental Screening Test in two-year old infants delivered by vacuum extraction - Meriah Sembiring; Iskandar Iskandar; Amir Syarifuddin; Bistok Saing (Indonesian Pediatric Society, 2001)
The aim of this study was to determine the developmental retardation of infants of two years of age who were delivered by vacuum extraction. This cross-sectional study examined 44 infants delivered by vacuum extraction, comprising 25 males and 19 females who were born in Tembakau Deli and St. Elizabeth Hospitals, between August 1993 until February 1994. The examination included interview and physical examination in the patient's house. Chi-square statistics analysis was used with a significant level of 95% (1'=0.05). The results showed Ihat of the 44 infants delivered by vacuum extraction. 28 (32%) had had were found with mild asphyxia, while 2 infants (5%). whose mothers work as private clerk and entrepreneur, had development retardation. We concluded that there was no significant difference in development between infants delivered by vacuum extraction and those who were born spontaneously. Developmental retardation was found in infants whose mothers lack time to communicate.